Preparation method and application of MnO2 nanosheet modified CoP / P-C nanotube electrode material
By modifying the MnO2 nanosheets on the CoP/P-C nanotube electrode material to form the electrode material with a composite structure, the problem of poor rate performance and Coulomb efficiency in the existing electrode materials in supercapacitors is solved, high specific capacitance, energy density and power density are achieved, and good cycling stability is achieved.
Patent Information
- Application Number
- CN202411650842.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
AI Technical Summary
Existing electrode materials have problems with poor rate performance and Coulomb efficiency in supercapacitors, especially the relatively poor conductivity of MnO2 limits the performance of the material.
The MnO2 nanosheets are modified on the CoP/P-C nanotube electrode material to form the electrode material of the composite structure. The method includes growing Co-MOF on a carbon cloth, followed by phosphating and MnO2 nanosheet modification to form a CoP/P-C/MnO2@CC electrode material.
The specific capacitance, energy density and power density of the electrode material were significantly improved, and in the cycle stability test, the specific capacitance retention rate of the material reached 77.3%, indicating that the material has good cycle stability.
Smart Images

Figure CN119517635A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrode materials, and relates to composite electrode materials, and in particular to a MnO 2 Preparation method and application of nanosheet modified CoP / PC nanotube electrode materials. Background Art
[0002] With the rapid development of industrial production and economic activities, the problems of energy shortage and environmental degradation are becoming increasingly serious. Therefore, the research on efficient, clean and safe energy storage devices is particularly important. Supercapacitors (SCs) are superior to many other energy storage devices due to their fast charging and discharging capabilities, long-term durability, high safety and high power density. It is worth noting that the design and preparation of electrode materials with large capacity, long-term stability and high energy density are crucial to improving the performance of supercapacitors. Therefore, it is necessary to develop high-performance electrode materials.
[0003] Metal organic frameworks (MOFs) are excellent precursors with adjustable pore size, high porosity and huge specific surface area. Doping can effectively improve the structure of the electrode and enhance its electrochemical performance, especially the doping of non-metallic elements. Adding heteroatoms to carbon materials can accelerate charge transfer and improve the interaction between the electrode and the electrolyte, thereby improving the electrochemical performance of the electrode. At the same time, doping with non-metallic elements can effectively improve the disadvantage of poor conductivity of carbon materials. Since the atomic radius of phosphorus is similar to that of oxygen, phosphorus doping can effectively improve the conductivity and increase the electrochemical reaction sites.
[0004] Among metal oxides, MnO 2 It is considered a particularly promising material due to its high capacity, abundance and non-toxicity. However, its relatively poor conductivity may hinder the material's rate performance and Coulombic efficiency. A possible solution is to integrate nanostructured MnO on a carbon matrix. 2 , in order to improve the conductivity and rate performance of the material. 2 The full contact with the electrolyte exposes a large number of active sites, thereby increasing the specific capacitance of the electrode material. In addition, the synergistic effect of the one-dimensional nanotubes and two-dimensional nanosheets in the electrode structure expands the specific surface area, shortens the ion and electron transmission channels, and thus improves the reaction kinetics. Therefore, for the metal oxide MnO 2 The research on nanosheet-modified electrode materials has great potential in high-performance supercapacitors. Summary of the invention
[0005] In order to overcome the defects of the prior art, the present invention discloses a MnO 2 Preparation method of nanosheet-modified CoP / PC nanotube electrode material.
[0006] Technical Solution
[0007] First, carbon cloth (CC) was prepared in the presence of cobalt source, 2-methylimidazole (C 4 H 6 N 2 ) was immersed in a mixed solution to obtain Co-MOF@CC, which was then calcined at high temperature to obtain CoP / PC@CC. Finally, CoP / PC / MnO was synthesized by solution immersion method. 2 @CC electrode material.
[0008] A MnO 2 Nanosheet modified CoP / PC (CoP / PC / MnO 2 @CC) A method for preparing a nanotube electrode material comprises the following steps:
[0009] A. Ultrasonicate a 0.05M cobalt source solution to form a uniform red transparent solution, add the dried pretreated carbon cloth (CC), and soak for 0.5 to 1.5 hours, preferably 1 hour; pour an equal volume of 0.4M 2-methylimidazole (2-IMM) solution, and continue soaking at 60°C for 2 to 4 hours, preferably 3 hours; cool naturally to room temperature after soaking, rinse the product with deionized water to remove residual solution and impurities, and dry at 60°C to obtain a rod-shaped Co-MOF (Co-MOF@CC) grown on the carbon cloth (CC);
[0010] B. Soak the Co-MOF@CC in a carbon source aqueous solution for 12 to 36 hours, preferably 24 hours, and dry at 60°C;
[0011] C. Place the dried sample and phosphorus source in two separate porcelain boats at the upstream and downstream ends of the tube furnace at a mass ratio of 1:5, and heat at a rate of 3°C / min under N 2 Calcination at 250-450℃ in atmosphere
[0012] 1 to 3 h, preferably calcined at 350 °C for 2 h to obtain CoP / PC@CC;
[0013] D. Immersing CoP / PC@CC into KMnO 4 The solution was immersed at 60℃ for 10-14h, preferably 12h, and the solution was cooled naturally at room temperature, filtered, washed with deionized water, and dried at 60℃ overnight to obtain CoP / PC /
[0014] MnO 2 @CC nanotube electrode materials.
[0015] In a preferred embodiment of the present invention, in step A, the cobalt source is Co(NO 3 ) 2 or CoCl 2 , preferably Co(NO3 ) 2 .
[0016] According to a preferred embodiment of the present invention, in step A, the pretreated carbon cloth (CC) is ultrasonically cleaned with deionized water and dried for later use.
[0017] According to a preferred embodiment of the present invention, in step B, the carbon source is glucose or citric acid, preferably glucose.
[0018] According to a preferred embodiment of the present invention, in step B, the concentration of the carbon source aqueous solution is 1 g / 10 mL to 1 g / mL.
[0019] In a preferred embodiment of the present invention, in step C, the phosphorus source is NaH 2 PO 2 , KH 2 PO 4 or K 2 HPO 4 , preferably NaH 2 PO 2 .
[0020] In a preferred embodiment of the present invention, in step D, the KMnO 4 The concentration of the solution is 0.01~0.03M.
[0021] CoP / PC / MnO prepared by the method of the present invention 2 @CC nanotube electrode material, the microstructure has two-dimensional MnO 2 Composite structures of nanosheets and one-dimensional CoP / PC core-shell nanotubes.
[0022] The second object of the present invention is to provide the prepared CoP / PC / MnO 2 @CC Application of nanotube electrode materials as positive electrode materials for supercapacitors.
[0023] The prepared CoP / PC / MnO 2 @CC nanotube electrode material was used as the positive electrode of the supercapacitor, 6 mol / L KOH was used as the electrolyte, activated carbon, acetylene black and binder were uniformly mixed in a mass ratio of 8:1:1, and then N-methylpyrrolidone was added and mixed and ground. After grinding, the slurry was coated on nickel foam and dried as the negative electrode material of the supercapacitor. The electrochemical performance tests such as cyclic voltammetry (CV), constant current charge and discharge (GCD) and electrochemical impedance spectroscopy (EIS) were carried out in the two-electrode system, and the corresponding specific capacitance, energy density and power density were calculated to evaluate the prepared CoP / PC / MnO 2@CC Electrochemical properties of electrode materials. The voltage range of cyclic voltammetry (CV) test is 0-0.45V, the scan rates are 2, 5, 10, 20, 50 and 100mV / s, and the voltage range of constant current charge and discharge (GCD) test is 0-0.5V, the current density is 1, 2, 3, 5, 8 and 10A / g.
[0024] CoP / PC / MnO prepared by the present invention 2 @CC electrode materials use field emission scanning electron microscopy (FE-SEM), CHI760E electrochemical workstation and other instruments to carry out structural characterization and performance analysis of the products to evaluate their electrochemical properties.
[0025] The reactants and reagents used in the present invention are all commercially available and of analytical grade.
[0026] Beneficial Effects
[0027] The present invention synthesizes CoP / PC / MnO by solution impregnation method and high temperature phosphating method 2 @CC electrode material, with carbon cloth (CC) as the substrate, gives the electrode material obvious flexibility and self-supporting properties. 2 @CC electrode materials have hollow nanorods and MnO 2 The composite structure of the nanosheets and the unique combination of the two structures shorten the transmission distance of ions and electrons and significantly increase the active sites. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 . CoP / PC / MnO prepared in Example 1 2 @CC Field emission scanning electron microscopy image of electrode material,
[0029] Figure 2 . Example 1 CoP / PC / MnO prepared 2 @CC GCD curve of electrode material,
[0030] Figure 3 . Example 1 CoP / PC / MnO prepared 2 @CC Electrode material assembled supercapacitor energy density-power density diagram,
[0031] Figure 4 . Example 1 CoP / PC / MnO prepared 2 @CC Cycling stability performance diagram of supercapacitors assembled with electrode materials. DETAILED DESCRIPTION
[0032] The present invention is described in detail below in conjunction with the embodiments so that those skilled in the art can better understand the present invention, but the present invention is not limited to the following embodiments.
[0033] Unless otherwise defined, the terms (including technical terms) used herein should be interpreted as having the same meaning as commonly understood by those skilled in the art to which the present invention belongs. It will also be understood that the terms used herein should be interpreted as having the meaning consistent with their meanings in the content of this specification and related technologies, and should not be interpreted in an idealized or excessive form unless specifically defined as such herein.
[0034] Example 1
[0035] A MnO 2 Nanosheet modified CoP / PC (CoP / PC / MnO 2 @CC) A method for preparing a nanotube electrode material comprises the following steps:
[0036] 1. Ultrasonic clean the carbon cloth (CC) with deionized water and dry it for later use; 0.582gCo(NO 3 ) 2 6H 2 O was ultrasonically dissolved in 40 mL of deionized water to form a uniform red transparent solution; after soaking the dried carbon cloth (CC) at room temperature for 1 h, 2-methylimidazole (2-IMM) solution (1.32 g 2-MIM, 40 mL of deionized water) was added to the mixed system, and then soaked at 60 ° C for another 3 h, cooled naturally to room temperature, washed with deionized water, and dried to obtain the rod-shaped Co-MOF (Co-MOF@CC) grown on the carbon cloth (CC);
[0037] 2. Weigh 4 g of glucose and dissolve it in 40 mL of deionized water by ultrasonication. Soak the prepared Co-MOF@CC in it at room temperature for 24 h and dry it. Mix the dried sample with NaH 2 PO 2 ·H 2 O (mass ratio of 1:5) were placed in two separate porcelain boats at the upstream and downstream ends of the tube furnace, respectively. 2 In the atmosphere, the heating rate was 3 °C / min, and CoP / PC@CC was obtained after calcination at 350 °C for 2 h;
[0038] 3. Weigh 0.0790g KMnO 4 Dissolve in 50 mL of deionized water and stir for 15 min to form a uniform KMnO 4 Solution; immerse in CoP / PC@CC, soak at 60℃ for 12h, cool naturally to room temperature, wash with deionized water, and dry at 60℃ overnight to obtain CoP / PC / MnO 2 @CC.
[0039] CoP / PC / MnO2 @CC electrode material characterization and analysis
[0040] like Figure 1 As shown, we can see CoP / PC / MnO 2 @CC The electrode material is composed of two-dimensional nanosheets and one-dimensional core-shell nanotubes in the microscopic state, forming a unique composite structure.
[0041] like Figure 2 As shown in the figure, it can be seen that CoP / PC / MnO 2 @CC GCD curve of electrode material.
[0042] like Figure 3 As shown, the CoP / PC / MnO prepared in this example 2 @CC electrode material is used as the positive electrode of supercapacitor in the two-electrode system. From the energy density-power density diagram, it can be seen that the assembled supercapacitor has good power density and energy density. When the maximum energy density reaches 93.12Wh / kg, its power density is 800W / kg.
[0043] like Figure 4 As shown, the CoP / PC / MnO prepared in this example 2 @CC The supercapacitor assembled with nanotube electrode materials was tested for cycle stability. After 8,000 cycles, its specific capacitance remained at 77.3% of the initial capacity.
[0044] Example 2
[0045] A MnO 2 The preparation method of the supercapacitor electrode material of nanosheet-modified CoP / PC nanotubes comprises the following steps:
[0046] Step 1: ultrasonically clean the pretreated carbon cloth (CC) with deionized water and dry it for later use; 0.582 g Co(NO 3 ) 2 6H 2 O was ultrasonically dissolved in 40 mL of deionized water to form a uniform red transparent solution; after soaking the dried carbon cloth (CC) at room temperature for 0.5 h, 2-methylimidazole (2-IMM) solution (1.32 g 2-MIM, 40 mL of deionized water) was added to the mixed system, and then soaked at 60 ° C for another 4 h, naturally cooled to room temperature, washed with deionized water, and dried to obtain the rod-shaped Co-MOF (Co-MOF@CC) grown on the carbon cloth (CC);
[0047] Step 2: Weigh 4 g of glucose and dissolve it in 40 mL of deionized water. Soak the prepared Co-MOF@CC in the water at room temperature for 36 h and dry it. 2 PO 2 ·H 2 O (mass ratio of 1:5) were placed in two separate porcelain boats at the upstream and downstream ends of the tube furnace. 2 Under the atmosphere, the heating rate was 3 °C / min and the reaction temperature was 250 °C. After calcination for 3 h, CoP / PC@CC was obtained.
[0048] Step 3: Weigh 0.0790 g KMnO 4 Dissolve in 50 mL of deionized water and stir for 15 min to form a uniform KMnO 4 Solution; immerse in CoP / PC@CC, soak at 60℃ for 14h, cool naturally to room temperature, wash with deionized water, and dry at 60℃ overnight to obtain CoP / PC / MnO 2 @CC.
[0049] The prepared CoP / PC / MnO 2 @CC The supercapacitor assembled with nanotube electrode materials was tested for cycle stability. After 8,000 cycles, its specific capacitance remained at 69.7% of the initial capacity.
[0050] Example 3
[0051] A MnO 2 The preparation method of the supercapacitor electrode material of nanosheet-modified CoP / PC nanotubes comprises the following steps:
[0052] Step 1: ultrasonically clean the pretreated carbon cloth (CC) with deionized water and dry it for later use; 0.582 g Co(NO 3 ) 2 6H 2 O was ultrasonically dissolved in 40 mL of deionized water to form a uniform red transparent solution; after soaking the dried carbon cloth (CC) at room temperature for 1.5 h, 2-methylimidazole (2-IMM) solution (1.32 g 2-MIM, 40 mL of deionized water) was added to the mixed system, and then soaked at 60 ° C for another 2 h, cooled naturally to room temperature, washed with deionized water, and dried to obtain the rod-shaped Co-MOF (Co-MOF@CC) grown on the carbon cloth (CC);
[0053] Step 2: Weigh 10 g of glucose and dissolve it in 10 mL of deionized water. Soak the prepared Co-MOF@CC in deionized water at room temperature for 12 h and dry it. 2 PO2 ·H 2 O (mass ratio of 1:5) were placed in two separate porcelain boats at the upstream and downstream ends of the tube furnace. 2 Under the atmosphere, the heating rate was 3 °C / min and the reaction temperature was 450 °C. After calcination for 1 h, CoP / PC@CC was obtained.
[0054] Step 3: Weigh 0.1896 g KMnO 4 Dissolve in 40 mL of deionized water and stir for 15 min to form a uniform KMnO 4 Solution; immerse in CoP / PC@CC, soak at 60℃ for 10h, cool naturally to room temperature, wash with deionized water, and dry at 60℃ overnight to obtain CoP / PC / MnO 2 @CC.
[0055] The prepared CoP / PC / MnO 2 @CC The supercapacitor assembled with nanotube electrode materials was tested for cycle stability. After 8,000 cycles, its specific capacitance remained at 62.1% of the initial capacity.
[0056] Example 4
[0057] A MnO 2 The preparation method of the supercapacitor electrode material of nanosheet-modified CoP / PC nanotubes comprises the following steps:
[0058] Step 1: ultrasonically clean the pretreated carbon cloth (CC) with deionized water and dry it for later use; 0.582 g Co(NO 3 ) 2 6H 2 O was ultrasonically dissolved in 40 mL of deionized water to form a uniform red transparent solution; after soaking the dried carbon cloth (CC) at room temperature for 1 h, 2-methylimidazole (2-IMM) solution (1.32 g 2-MIM, 40 mL of deionized water) was added to the mixed system, and then soaked at 60 ° C for another 3 h, cooled naturally to room temperature, washed with deionized water, and dried to obtain the rod-shaped Co-MOF (Co-MOF@CC) grown on the carbon cloth (CC);
[0059] Step 2: Weigh 4 g of citric acid and dissolve it in 40 mL of deionized water, and then ultrasonically homogenize it. Then soak the prepared Co-MOF@CC in it at room temperature for 24 h and dry it. 2 PO 4 The two ceramic boats (mass ratio of 1:5) were placed in two separate porcelain boats at the upstream and downstream ends of the tube furnace. 2Under the atmosphere, the heating rate was 3 °C / min and the reaction temperature was 350 °C. After calcination for 2 h, CoP / PC@CC was obtained.
[0060] Step 3: Weigh 0.0790 g KMnO 4 Dissolve in 50 mL of deionized water and stir for 15 min to form a uniform KMnO 4 Solution; immerse in CoP / PC@CC, soak at 60℃ for 12h, cool naturally to room temperature, wash with deionized water, and dry at 60℃ overnight to obtain CoP / PC / MnO 2 @CC.
[0061] The prepared CoP / PC / MnO 2 @CC The supercapacitor assembled with nanotube electrode materials was tested for cycle stability. After 8,000 cycles, its specific capacitance remained at 59.3% of the initial capacity.
[0062] Example 5
[0063] A MnO 2 The preparation method of the supercapacitor electrode material of nanosheet-modified CoP / PC nanotubes comprises the following steps:
[0064] Step 1: ultrasonically clean the pretreated carbon cloth (CC) with deionized water and dry it for later use; 0.476 g CoCl 2 6H 2 O was ultrasonically dissolved in 40 mL of deionized water to form a uniform red transparent solution; after soaking the dried carbon cloth (CC) at room temperature for 0.5 h, 2-methylimidazole (2-IMM) solution (1.32 g 2-MIM, 40 mL of deionized water) was added to the mixed system, and then soaked at 60 ° C for another 4 h, naturally cooled to room temperature, washed with deionized water, and dried to obtain the rod-shaped Co-MOF (Co-MOF@CC) grown on the carbon cloth (CC);
[0065] Step 2: Weigh 4 g of citric acid and dissolve it in 40 mL of deionized water, and then ultrasonically homogenize it. Then soak the prepared Co-MOF@CC in it at room temperature for 36 h and dry it. 2 PO 4 The two ceramic boats (mass ratio of 1:5) were placed in two separate porcelain boats at the upstream and downstream ends of the tube furnace. 2 Under the atmosphere, the heating rate was 3 °C / min and the reaction temperature was 250 °C. After calcination for 3 h, CoP / PC@CC was obtained.
[0066] Step 3: Weigh 0.0790 g KMnO 4Dissolve in 50 mL of deionized water and stir for 15 min to form a uniform KMnO 4 Solution; immerse in CoP / PC@CC, soak at 60℃ for 14h, cool naturally to room temperature, wash with deionized water, and dry at 60℃ overnight to obtain CoP / PC / MnO 2 @CC.
[0067] The prepared CoP / PC / MnO 2 @CC The supercapacitor assembled with nanotube electrode materials was tested for cycle stability. After 8,000 cycles, its specific capacitance remained at 55.2% of the initial capacity.
[0068] Example 6
[0069] A MnO 2 The preparation method of the supercapacitor electrode material of nanosheet-modified CoP / PC nanotubes comprises the following steps:
[0070] Step 1: ultrasonically clean the pretreated carbon cloth (CC) with deionized water and dry it for later use; 0.476 g CoCl 2 6H 2 O was ultrasonically dissolved in 40 mL of deionized water to form a uniform red transparent solution; after soaking the dried carbon cloth (CC) at room temperature for 1 h, 2-methylimidazole (2-IMM) solution (1.32 g 2-MIM, 40 mL of deionized water) was added to the mixed system, and then soaked at 60 ° C for another 3 h, cooled naturally to room temperature, washed with deionized water, and dried to obtain the rod-shaped Co-MOF (Co-MOF@CC) grown on the carbon cloth (CC);
[0071] Step 2: Weigh 4 g of citric acid and dissolve it in 40 mL of deionized water, and then ultrasonically homogenize it. Then soak the prepared Co-MOF@CC in it at room temperature for 24 h and dry it. 2 PO 4 The two ceramic boats (mass ratio of 1:5) were placed in two separate porcelain boats at the upstream and downstream ends of the tube furnace. 2 Under the atmosphere, the heating rate was 3 °C / min and the reaction temperature was 350 °C. After calcination for 2 h, CoP / PC@CC was obtained.
[0072] Step 3: Weigh 0.0790 g KMnO 4 Dissolve in 50 mL of deionized water and stir for 15 min to form a uniform KMnO 4 Solution; immerse in CoP / PC@CC, soak at 60℃ for 12h, cool naturally to room temperature, wash with deionized water, and dry at 60℃ overnight to obtain CoP / PC / MnO 2 @CC.
[0073] The prepared CoP / PC / MnO 2 @CC The supercapacitor assembled with nanotube electrode materials was tested for cycle stability. After 8,000 cycles, its specific capacitance remained at 70.7% of the initial capacity.
[0074] Example 7
[0075] A MnO 2 The preparation method of the supercapacitor electrode material of nanosheet-modified CoP / PC nanotubes comprises the following steps:
[0076] Step 1: ultrasonically clean the pretreated carbon cloth (CC) with deionized water and dry it for later use; 0.476 g CoCl 2 6H 2 O was ultrasonically dissolved in 40 mL of deionized water to form a uniform red transparent solution; after soaking the dried carbon cloth (CC) at room temperature for 1.5 h, 2-methylimidazole (2-IMM) solution (1.32 g 2-MIM, 40 mL of deionized water) was added to the mixed system, and then soaked at 60 ° C for another 2 h, cooled naturally to room temperature, washed with deionized water, and dried to obtain the rod-shaped Co-MOF (Co-MOF@CC) grown on the carbon cloth (CC);
[0077] Step 2: Weigh 10 g of citric acid and dissolve it in 10 mL of deionized water, and then ultrasonically homogenize it. Then soak the prepared Co-MOF@CC in it at room temperature for 12 h and dry it. 2 PO 4 The two ceramic boats (mass ratio of 1:5) were placed in two separate porcelain boats at the upstream and downstream ends of the tube furnace. 2 Under the atmosphere, the heating rate was 3 °C / min and the reaction temperature was 450 °C. After calcination for 1 h, CoP / PC@CC was obtained.
[0078] Step 3: Weigh 0.1896 g KMnO 4 Dissolve in 40 mL of deionized water and stir for 15 min to form a uniform KMnO 4 Solution; immerse in CoP / PC@CC, soak at 60℃ for 10h, cool naturally to room temperature, wash with deionized water, and dry at 60℃ overnight to obtain CoP / PC / MnO 2 @CC.
[0079] The prepared CoP / PC / MnO 2 @CC The supercapacitor assembled with nanotube electrode materials was tested for cycle stability. After 8,000 cycles, its specific capacitance remained at 43.8% of the initial capacity.
[0080] Example 8
[0081] A MnO 2 The preparation method of the supercapacitor electrode material of nanosheet-modified CoP / PC nanotubes comprises the following steps:
[0082] Step 1: ultrasonically clean the pretreated carbon cloth (CC) with deionized water and dry it for later use; 0.476 g CoCl 2 6H 2 O was ultrasonically dissolved in 40 mL of deionized water to form a uniform red transparent solution; after soaking the dried carbon cloth (CC) at room temperature for 1 h, 2-methylimidazole (2-IMM) solution (1.32 g 2-MIM, 40 mL of deionized water) was added to the mixed system, and then soaked at 60 ° C for another 3 h, cooled naturally to room temperature, washed with deionized water, and dried to obtain the rod-shaped Co-MOF (Co-MOF@CC) grown on the carbon cloth (CC);
[0083] Step 2: Weigh 4 g of glucose and dissolve it in 40 mL of deionized water. Soak the prepared Co-MOF@CC in the water at room temperature for 24 h and dry it. 2 PO 2 ·H 2 O (mass ratio of 1:5) were placed in two separate porcelain boats at the upstream and downstream ends of the tube furnace. 2 Under the atmosphere, the heating rate was 3 °C / min and the reaction temperature was 350 °C. After calcination for 2 h, CoP / PC@CC was obtained.
[0084] Step 3: Weigh 0.0790 g KMnO 4 Dissolve in 50 mL of deionized water and stir for 15 min to form a uniform KMnO 4 Solution; immerse in CoP / PC@CC, soak at 60℃ for 12h, cool naturally to room temperature, wash with deionized water, and dry at 60℃ overnight to obtain CoP / PC / MnO 2 @CC.
[0085] The CoP / PC / MnO prepared in this example 2 @CC The supercapacitor assembled with nanotube electrode materials was tested for cycle stability. After 8,000 cycles, its specific capacitance remained at 70.1% of the initial capacity.
[0086] Example 9
[0087] A MnO 2 The preparation method of the supercapacitor electrode material of nanosheet-modified CoP / PC nanotubes comprises the following steps:
[0088] Step 1: ultrasonically clean the pretreated carbon cloth (CC) with deionized water and dry it for later use; 0.476 g CoCl 2 6H 2 O was ultrasonically dissolved in 40 mL of deionized water to form a uniform red transparent solution; after soaking the dried carbon cloth (CC) at room temperature for 1 h, 2-methylimidazole (2-IMM) solution (1.32 g 2-MIM, 40 mL of deionized water) was added to the mixed system, and then soaked at 60 ° C for another 3 h, cooled naturally to room temperature, washed with deionized water, and dried to obtain the rod-shaped Co-MOF (Co-MOF@CC) grown on the carbon cloth (CC);
[0089] Step 2: Weigh 4 g of glucose and dissolve it in 40 mL of deionized water, and then ultrasonically homogenize it. Then soak the prepared Co-MOF@CC in the water at room temperature for 24 h and dry it. 2 HPO 4 ·3H 2 O (mass ratio of 1:5) were placed in two separate porcelain boats at the upstream and downstream ends of the tube furnace. 2 Under the atmosphere, the heating rate was 3 °C / min and the reaction temperature was 350 °C. After calcination for 2 h, CoP / PC@CC was obtained.
[0090] Step 3: Weigh 0.0790 g KMnO 4 Dissolve in 50 mL of deionized water and stir for 15 min to form a uniform KMnO 4 Solution; immerse in CoP / PC@CC, soak at 60℃ for 12h, cool naturally to room temperature, wash with deionized water, and dry at 60℃ overnight to obtain CoP / PC / MnO 2 @CC.
[0091] The prepared CoP / PC / MnO 2 @CC The supercapacitor assembled with nanotube electrode materials was tested for cycle stability. After 8,000 cycles, its specific capacitance remained at 68.5% of the initial capacity.
[0092] Example 10
[0093] A MnO 2 The preparation method of the supercapacitor electrode material of nanosheet-modified CoP / PC nanotubes comprises the following steps:
[0094] Step 1: ultrasonically clean the pretreated carbon cloth (CC) with deionized water and dry it for later use; 0.582 g Co(NO 3 ) 2 6H2 O was ultrasonically dissolved in 40 mL of deionized water to form a uniform red transparent solution; after soaking the dried carbon cloth (CC) at room temperature for 1 h, 2-methylimidazole (2-IMM) solution (1.32 g 2-MIM, 40 mL of deionized water) was added to the mixed system, and then soaked at 60 ° C for another 3 h, cooled naturally to room temperature, washed with deionized water, and dried to obtain the rod-shaped Co-MOF (Co-MOF@CC) grown on the carbon cloth (CC);
[0095] Step 2: Weigh 4 g of glucose and dissolve it in 40 mL of deionized water, and then ultrasonically homogenize it. Then soak the prepared Co-MOF@CC in the water at room temperature for 24 h and dry it. 2 HPO 4 ·3H 2 O (mass ratio of 1:5) were placed in two separate porcelain boats at the upstream and downstream ends of the tube furnace. 2 Under the atmosphere, the heating rate was 3 °C / min and the reaction temperature was 350 °C. After calcination for 2 h, CoP / PC@CC was obtained.
[0096] Step 3: Weigh 0.0790 g KMnO 4 Dissolve in 50 mL of deionized water and stir for 15 min to form a uniform KMnO 4 Solution; immerse in CoP / PC@CC, soak at 60℃ for 12h, cool naturally to room temperature, wash with deionized water, and dry at 60℃ overnight to obtain CoP / PC / MnO 2 @CC.
[0097] The prepared CoP / PC / MnO 2 @CC The supercapacitor assembled with nanotube electrode materials was tested for cycle stability. After 8,000 cycles, its specific capacitance remained at 72.4% of the initial capacity.
[0098] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a MnO2 nanosheet-modified CoP / PC nanotube electrode material, characterized in that: The following steps are involved: A. Ultrasonicate a 0.05 M cobalt source solution to form a uniform red transparent solution, add the dried pretreated carbon cloth, and soak for 0.5-1.5 h; pour an equal volume of 0.4 M 2-methylimidazole solution, and continue soaking at 60 ° C for 2-4 h; cool naturally to room temperature after soaking, rinse the product with deionized water to remove the residual solution and impurities, and dry at 60 ° C to obtain a rod-shaped Co-MOF grown on the carbon cloth, namely Co-MOF@CC; B. Soak the Co-MOF@CC in a carbon source aqueous solution for 12 to 36 hours and dry at 60°C; C. The dried sample and phosphorus source were placed in two separate porcelain boats at the upstream and downstream ends of the tube furnace at a mass ratio of 1:5, respectively. The heating rate was 3°C / min, and CoP / PC@CC was obtained after calcination at 250-450°C for 1-3h in a N2 atmosphere. D. Immerse CoP / PC@CC in KMnO4 solution at 60°C for 10 to 14 hours, preferably 12 hours, allow the solution to cool naturally to room temperature, filter, wash with deionized water, and dry at 60°C overnight to obtain CoP / PC / MnO2@CC nanotube electrode material, wherein the concentration of the KMnO4 solution is 0.01 to 0.03M.
2. The method for preparing the MnO2 nanosheet-modified CoP / PC nanotube electrode material according to claim 1, characterized in that: In step A, 0.05 M cobalt source solution was ultrasonically treated to form a uniform red transparent solution, and the dried pretreated carbon cloth was added and soaked for 1 h; an equal volume of 0.4 M 2-methylimidazole solution was poured into the solution and soaked at 60° C. for another 3 h.
3. The method for preparing the MnO2 nanosheet-modified CoP / PC nanotube electrode material according to claim 1, characterized in that: In step A, the cobalt source is Co(NO3)2 or CoCl2, preferably Co(NO3)2.
4. The method for preparing the MnO2 nanosheet-modified CoP / PC nanotube electrode material according to claim 1, characterized in that: In step A, the pretreated carbon cloth is ultrasonically cleaned with deionized water and dried for later use.
5. The method for preparing the MnO2 nanosheet-modified CoP / PC nanotube electrode material according to claim 1, characterized in that: In step B, the Co-MOF@CC was immersed in a carbon source aqueous solution for 24 h.
6. The method for preparing the MnO2 nanosheet-modified CoP / PC nanotube electrode material according to claim 1, characterized in that: In step B, the carbon source is glucose or citric acid, preferably glucose.
7. The method for preparing the MnO2 nanosheet-modified CoP / PC nanotube electrode material according to claim 1, characterized in that: In step C, the dried sample and the phosphorus source were placed in two separate porcelain boats at the upstream and downstream ends of the tube furnace in a mass ratio of 1:5, respectively. The heating rate was 3°C / min, and CoP / PC@CC was obtained after calcination at 350°C for 2h in a N2 atmosphere.
8. The method for preparing the MnO2 nanosheet-modified CoP / PC nanotube electrode material according to claim 1, characterized in that: In step C, the phosphorus source is NaH2PO2, KH2PO4 or K2HPO4, preferably NaH2PO2.
9. The MnO2 nanosheet-modified CoP / PC nanotube electrode material prepared according to any one of claims 1 to 8, characterized in that: Its microstructure has a composite structure of two-dimensional MnO2 nanosheets and one-dimensional CoP / PC core-shell nanotubes.
10. An application of the MnO2 nanosheet modified CoP / PC nanotube electrode material as claimed in claim 9, characterized in that: It is applied to supercapacitor positive electrode materials.